Correlation of age to classification of vertical relationship of maxillary sinus and maxillary first molar root by cone-beam computed tomography: a cross-sectional study - Suntana, Mutiara Sukma; Darwis, Rudi Satria; Nissa, Rena Izzatin; Trisusanti, Ratna (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: The maxillary first molar has a close relationship with the base of the maxillary sinus floor. Cone-beam Computed Tomography (CBCT) provides coronal, sagittal, occlusal, and 3D sectional images of maxillofacial structures without causing distortion. Thus, CBCT allows for a comprehensive analysis of the position of the maxillary first molar about the maxillary sinus. This study aims to determine the correlation between age and the classification of vertical relationship between the maxillary sinus and the roots of the maxillary first molar using CBCT. Materials and Methods: The research design was the analytical observational research used a cross-sectional design. The study population includes all CBCT radiographs from patients aged 20-50 years who used CBCT at RSGMP Universitas Jenderal Achmad Yani. The total sampling technique was used to include all CBCT radiograph data comforms to the inclusion and exclusion criteria. Results: The study resulted in 60 CBCT radiographs, with 54 data for the right maxillary first molar and 49 data for the left maxillary first molar. Data analysis using Spearman correlation test showed r = -0.191 with a p-value of 0.166 for the right maxillary first molar and r = -0.167 with a p-value of 0.252 for the left maxillary first molar. Conclusion: There was no correlation between age and the classification of vertical relationship between the maxillary sinus and the maxillary first molar tooth root (p > 0.05). This is because the volume of the maxillary sinus decreases with age, leading to an increased distance between the maxillary sinus and the tooth roots.